Molybdenum diselenide nano carbon material compound, preparation method thereof and hydrogen evolution catalytic electrode
By preparing the molybdenum diselenide nanocarbon material composite, the problem of low catalytic activity of existing transition metal diazide is solved, and a hydrogen evolution reaction catalyst with a catalytic activity close to or better than platinum is achieved, with excellent electronic performance and economicality.
Patent Information
- Application Number
- CN202411904771.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-07
AI Technical Summary
The existing transition metal disulfides have low catalytic activity in hydrogen evolution reactions, mainly due to the low conductivity and difficulty in controlling the nanostructure size, resulting in limited electron transfer.
By preparing a composite of molybdenum diselenide nanocarbon material, the nanomolybdenum diselenide particles were dispersed on the nanocarbon material by sonication, and the size of the molybdenum diselenide particles was controlled to maximize catalytic activity.
A hydrogen evolution reaction catalyst with a catalytic activity close to or better than platinum is achieved, and has excellent electronic properties and economicality.
Smart Images

Figure CN119392300A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molybdenum diselenide nano-carbon material composite and a preparation method thereof, and a hydrogen evolution catalytic electrode, belonging to the field of hydrogen evolution catalysts. Background Art
[0002] Hydrogen is one of the most environmentally friendly and efficient energy sources that can replace fossil fuels and has received great attention. Electrocatalytic water splitting to produce hydrogen has been widely studied, and platinum is the most well-known electrocatalyst for the hydrogen evolution reaction (HER). However, due to the scarcity and high cost of platinum, its use in large-scale processes is limited, so people are working hard to develop high-performance catalyst materials with abundant raw materials, high economic efficiency, and comparable performance to platinum in the hydrogen evolution reaction.
[0003] In recent years, two-dimensional transition metal dichalcogenides have been intensively studied in various application fields such as solar cells, light-emitting diodes, gas sensors and hydrogen evolution reaction. Their performance as hydrogen evolution reaction catalysts has been demonstrated by many studies, showing their potential in practical applications. For example, hafnium diselenide (Hf2Se) containing hafnium (Hf) and selenium (Se) 0.9 ).
[0004] However, the transition metal disulfides developed so far have low catalytic activity due to their low conductivity and limited electron transfer between the electrode and the electrocatalyst. To solve this problem, researchers have tried to combine conductive materials such as porous carbon with metal oxides, but since most of the transition metal disulfides in these studies are grown in situ on the surface of conductive materials, their nanostructure size is difficult to control and the degree of improvement in catalytic activity is limited. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a molybdenum diselenide nano-carbon material composite and a preparation method thereof, and provides a hydrogen evolution catalytic electrode containing the composite. The raw materials are abundant and low in price, and the catalytic activity is close to or better than that of a platinum hydrogen evolution reaction catalyst.
[0006] The technical solution adopted by the present invention to solve its technical problem is: In a first aspect, the present application provides a method for preparing a molybdenum diselenide nano-carbon material composite, comprising the following steps: preparing a nanocarbon material dispersion; preparing a dispersion of nano-molybdenum diselenide particles; Mixing the nano-carbon material dispersion and the nano-molybdenum diselenide particle dispersion, ultrasonically treating, filtering and drying to obtain the molybdenum diselenide nano-carbon material composite; The steps of preparing the nano-molybdenum diselenide particle dispersion liquid include: A molybdenum precursor solution at room temperature is added dropwise to a selenium precursor solution at 150°C to 200°C, and then heat-treated at 200°C to 250°C to obtain molybdenum diselenide particles after impurity removal. The molybdenum diselenide particles are dispersed in a second solvent to obtain the nano molybdenum diselenide particle dispersion.
[0007] In the preparation method of molybdenum diselenide nano-carbon material composite provided in the present application, MoSe2 particles are formed by mixing a hot selenium precursor solution with high activity and a room-temperature molybdenum precursor solution at room temperature and subjecting to heat treatment. The molybdenum element and the selenium element can react quickly and directly to form a precursor mixture, which has higher thermodynamic efficiency and is more conducive to the formation of stable MoSe2 particles.
[0008] Optionally, the second solvent is dimethylformamide.
[0009] Optionally, the ultrasonic treatment is performed at room temperature for 1 hour.
[0010] Optionally, the nano-molybdenum diselenide particles are in the shape of flakes.
[0011] Furthermore, the average size of the nano-molybdenum diselenide particles is 1 nm to 20 nm.
[0012] Furthermore, the molybdenum diselenide particles having a size of 2 nm to 16 nm account for 95% to 98% of the total number of the molybdenum diselenide particles.
[0013] Furthermore, in the step of mixing the nano-carbon material dispersion and the nano-molybdenum diselenide particle dispersion, the mass ratio of the nano-carbon material in the nano-carbon material dispersion to the nano-molybdenum diselenide particles in the nano-molybdenum diselenide particle dispersion is 100:25-400.
[0014] Further, the solvent of the selenium precursor solution and the solvent of the molybdenum precursor solution are selected from at least one of oleic acid, oleylamine, dodecyl mercaptan, acetone, p-xylene and n-octane. Oleic acid, oleylamine and dodecyl mercaptan not only have the basic function of solvent, but also can act as a crystallization regulator of reactants, because functional groups such as carboxyl, amine and thiol groups in their structures can be combined on the particle surface to stabilize the particles. In particular, the unsaturated selenium atoms at the edge of MoSe2 show a higher catalytic activity than the basal plane in the hydrogen evolution reaction. When oleic acid and oleylamine are used as solvents, the formation of MoSe2 particles with a porous structure can be promoted, which is conducive to exposing more particles with active edges. In addition, when acetone is used as a solvent, the reaction efficiency between reactants can be improved by increasing the solubility of low-solubility raw materials.
[0015] Furthermore, the solute of the selenium precursor solution is selenium powder, and the solvent of the selenium precursor solution is a 9:1 mixture of oleylamine and dodecyl mercaptan by volume.
[0016] Furthermore, the solute of the molybdenum precursor solution is molybdenum hexacarbonyl, and the solvent of the molybdenum precursor solution is a 3:4 mixture of oleic acid and acetone by volume.
[0017] Furthermore, the step of heat treatment at 200°C-250°C includes: heating to 200°C and keeping the temperature for 30 minutes for a first heat treatment, and then heating to 250°C and keeping the temperature for 30 minutes for a second heat treatment.
[0018] Optionally, the nano-carbon material in the nano-carbon material dispersion is graphene oxide or reduced graphene oxide.
[0019] Furthermore, the step of preparing the nano-carbon material dispersion comprises: Adding graphite powder and sodium nitrate to concentrated sulfuric acid containing potassium permanganate, stirring in an ice bath, then heating to 95° C., removing unreacted potassium permanganate with hydrogen peroxide, washing the reaction mixture with water, and then ultrasonically dispersing it in a first solvent to obtain a graphene oxide dispersion; Alternatively, L-ascorbic acid is continuously added to the graphene oxide dispersion to obtain a reduced graphene oxide dispersion after reaction.
[0020] Optionally, the first solvent is dimethylformamide.
[0021] In a second aspect, the present application provides a molybdenum diselenide nano-carbon material composite, which is prepared by the molybdenum diselenide nano-carbon material composite preparation method described in the first aspect.
[0022] The molybdenum diselenide nano-carbon material composite comprises a nano-carbon material and molybdenum diselenide particles dispersedly loaded on the nano-carbon material. The average size of the molybdenum diselenide particles is 1 nm to 20 nm, wherein the molybdenum diselenide particles of 2 nm to 16 nm account for 95% to 98% of the total number of the molybdenum diselenide particles.
[0023] In a third aspect, the present application provides a hydrogen evolution catalytic electrode comprising the molybdenum diselenide nano-carbon material composite as described in the second aspect.
[0024] The beneficial effects of the present invention are as follows: the present invention can maximize the catalytic activity by controlling the size of molybdenum diselenide particles, and utilizes ultrasound to disperse nano molybdenum diselenide particles on a nano carbon material with excellent electrical conductivity, thereby improving the problem of reduced activity and stability caused by agglomeration of nano molybdenum diselenide particles when used alone as a catalyst for a hydrogen evolution reaction. The present invention is more economical than a platinum catalyst, and at the same time has excellent electronic properties, exhibits excellent catalytic activity in a hydrogen evolution reaction, and can be used as an effective catalyst for a hydrogen evolution reaction.
[0025] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures particularly pointed out in the written description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an image of the MoSe2 particles of Preparation Example 2 observed under a scanning electron microscope.
[0027] Figure 2 This is the particle size distribution diagram of MoSe2 particles in Preparation Example 2.
[0028] Figure 3 These are the X-ray diffraction images of the MoSe2 particles of Preparation Example 2 and the nanocarbon materials of Preparation Example 1.
[0029] Figure 4 These are Raman spectral images of the MoSe2 particles of Preparation Example 2 and the nanocarbon materials of Preparation Example 1.
[0030] Figure 5 It is the X-ray photoelectron spectrum of MoSe2 particles of Preparation Example 2 and nanocarbon materials of Preparation Example 1.
[0031] Figure 6 This is an image of the nano-molybdenum diselenide particle dispersion prepared in the present application observed under a transmission electron microscope.
[0032] Figure 7 It is an energy dispersive X-ray spectrum image of the nano-molybdenum diselenide particle dispersion prepared in the present application.
[0033] Figure 8 These are electron microscope images taken by a field emission scanning electron microscope (FE-SEM) after Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 1, and Example 5 were coated on a silicon substrate.
[0034] Fig. 9 It is a comparison chart of the electrochemical characteristics of each embodiment and comparative example.
[0035] Fig.10 It is the Nyquist plot obtained after impedance testing of Comparative Example 3 and each embodiment.
[0036] Fig.11 The catalyst polarization curves of Examples 1 and 5 obtained at the initial stage of the hydrogen evolution reaction and after 1000 repetitions are shown. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] It should be understood that, under the premise of no conflict, any and all embodiments of the present invention can be combined with the technical features in any other embodiment or multiple other embodiments to obtain another embodiment. The present invention includes such a combination to obtain another embodiment.
[0039] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.
[0040] The present invention provides a method for preparing a molybdenum diselenide nano-carbon material composite, comprising the following steps: S1: preparing a nanocarbon material dispersion.
[0041] S2: Prepare nano-molybdenum diselenide particle dispersion.
[0042] S3: mixing the nano-carbon material dispersion and the nano-molybdenum diselenide particle dispersion, ultrasonically treating, filtering and drying to obtain a molybdenum diselenide nano-carbon material composite.
[0043] Step S2 specifically includes the following steps: preparing a molybdenum precursor solution using oleic acid and acetone as solvents; preparing a selenium precursor solution using oleylamine and dodecanethiol as solvents, and heating the selenium precursor solution to prepare a highly active selenium precursor solution; dropping the molybdenum precursor solution at room temperature into the highly active selenium precursor solution; and heating the mixed precursor solution to prepare MoSe2 particles.
[0044] Specifically, a molybdenum precursor solution at 22±2°C is slowly added to a selenium precursor solution activated at 150°C to 200°C, and the molybdenum element and the selenium element can react quickly and directly to form a precursor mixture, making it more thermodynamically efficient and forming stable MoSe2 particles. In the subsequent step S3, the MoSe2 particles are loaded on the nanocarbon material in an inherent form, rather than growing on the nanocarbon material. Finally, the size of the molybdenum diselenide nanocarbon material composite is easy to control, and the ratio of molybdenum diselenide and nanocarbon material is also easy to control, which is conducive to assembling a form with stronger hydrogen evolution reaction activity in the composite composed of molybdenum diselenide and nanocarbon material.
[0045] As an example, the molybdenum precursor solution uses a mixture of oleic acid and acetone in a volume ratio of 3:4 as a solvent, and the selenium precursor solution uses oleylamine and dodecanethiol in a volume ratio of 9:1 as a solvent, and the heat treatment of the obtained precursor mixed solution is carried out step by step. Specifically, the step of heat treating the mixed precursor solution prepared by the molybdenum precursor solution and the selenium precursor solution includes: adding the room temperature molybdenum precursor solution to the 150°C selenium precursor solution and heating it to 200°C, as a first heat treatment step; and, heating the mixed precursor solution to 250°C after keeping it at 200°C, as a second heat treatment step. By heat treating the precursor mixed solution step by step and continuously as above, MoSe2 particles of 20nm or less can be prepared.
[0046] Specifically, in the first heat treatment, the material was heated to 200° C. and then kept at that temperature for 30 minutes, and in the second heat treatment, the material was heated to 250° C. and then kept at that temperature for 30 minutes.
[0047] Combined with the above preferred conditions, the average size of the prepared MoSe2 particles is between 1nm and 20nm, and the occupancy rate of particles with an average size of 2nm to 16nm is 95%-98%. The MoSe2 particles are nanosheet structures and have more exposed edge active sites than bulk MoSe2.
[0048] In step S3, MoSe2 particles are dispersed on the surface of the nano-carbon material in a specific content, specifically, by mass, 25 to 400 parts of nano-molybdenum diselenide particles are added to every 100 parts of the nano-carbon material.
[0049] The present invention is further described below in conjunction with examples, but the following examples are only for detailed description of the present invention, and the content of the present invention is not limited to the following examples.
[0050] Preparation Example 1: Preparation of GO dispersion and rGO dispersion.
[0051] 0.5 g of graphite powder and 0.5 g of sodium nitrate (NaNO3) were added to a flask containing 3 g of potassium permanganate (KMnO4) and concentrated sulfuric acid (23 mL). The mixture was stirred in an ice bath for 2 h, and then the temperature of the reaction mixture was raised to 95 °C and maintained for 1 h. The suspension was then treated with hydrogen peroxide (H2O2, 10 mL, concentration 30%) to remove unreacted potassium permanganate. The resulting reaction mixture was washed with water (55 mL), dispersed in dimethylformamide (DMF), and finally ultrasonically dispersed to obtain a GO dispersion.
[0052] At the same time, a portion (50 mL) of the GO dispersion obtained above was taken out, L-ascorbic acid (L-AA, 50 mg) was added, and stirred for 48 hours to obtain an rGO dispersion with most of the oxygen-containing functional groups removed.
[0053] Preparation Example 2: Preparation of MoSe2 particles.
[0054] MoSe2 particles were prepared by a modified colloidal method. Specifically, a three-necked flask was fixed to a heating mantle, nitrogen (N2) was continuously introduced to maintain the N2 atmosphere in the flask, and then a mixed solution of oleylamine and dodecyl mercaptan mixed in a volume ratio of 9:1 and dissolved with 1.2mmol of selenium powder was injected. The mixed solution was heated to 120°C and stirred vigorously for 10 minutes to remove the generated water and oxygen, and then heated to 200°C and stirred continuously for 1 hour to obtain a transparent, bright yellow, highly active selenium precursor solution. At the same time, 0.6mmol of hexacarbonyl molybdenum (Mo(CO)6) was dissolved in a solution (21mL) of oleic acid and acetone mixed in a volume ratio of 3:4 to prepare a molybdenum precursor solution. After the highly active selenium precursor solution was cooled to 150°C, the molybdenum precursor solution was slowly added to the selenium precursor solution at a rate of 2 drops / second. After all the molybdenum precursor solution has been added, the mixture solution is heated to 200°C and maintained for 30 minutes for the first heat treatment, and then heated to 250°C and maintained for 30 minutes for the second heat treatment. After the end, the reaction mixture is cooled to room temperature, an excess of hexane is added, and the solid product is centrifuged and filtered. The filtered product is repeatedly washed with hexane and ethanol, and 30 mL of acetic acid is added and stirred at 85°C for 12 hours to remove all organic molecules in the product. Finally, the product is further washed with ethanol and centrifuged 3 times. The obtained solid product is dried in a vacuum oven at 50°C to obtain MoSe2 particles.
[0055] When oleic acid and oleylamine are used as solvents, the formation of MoSe2 particles with a porous structure can be promoted, which is conducive to exposing more active edge particles (unsaturated selenium atoms at the edge of MoSe2 show higher catalytic activity than the basal plane in the hydrogen evolution reaction). In addition, when acetone is used as a solvent, the reaction efficiency between the reactants can be improved by increasing the solubility of low-solubility raw materials. After slowly adding a molybdenum precursor solution to a highly active selenium precursor solution to form a large number of MoSe2 nuclei, further heat treatment is performed to obtain MoSe2 particles of 20nm or less.
[0056] The particle size distribution of the MoSe2 particles prepared in Preparation Example 2 was studied. The scanning electron microscopy (SEM) results of the MoSe2 particles prepared in Preparation Example 2 are as follows: Figure 1 The particle size distribution diagram of MoSe2 particles prepared in Preparation Example 2 is shown in Figure 2 As shown, Figure 2 The horizontal axis is the size, Figure 2 The ordinate is the number (only to reveal the relative proportion of particles of different sizes, not an absolute count, so the ordinate has no unit), Figure 2It can be found that most MoSe2 particles (≈100%) have an average size of 2nm to 16nm, with an average size of 6nm, among which particles with an average size of 2 to 8nm have a narrow particle size distribution, accounting for about 79.5±1% of all particles.
[0057] X-ray diffraction (XRD) analysis: Using a Bruker X-ray diffractometer, the GO and rGO particles prepared in Preparation Example 1 and the MoSe2 particles prepared in Preparation Example 2 were irradiated with radiation of a wavelength of 1.5406Å at a rate of 0.02° / s in the range of 2θ of 0 to 90° to obtain the following XRD results: Figure 3 The results shown, Figure 3 The abscissa of is the angle between the incident X-ray beam and the diffraction detector, in degrees; Figure 3 The ordinate is relative intensity, in arbitrary units. Figure 3 (a) is the X-ray diffraction pattern of GO and rGO. The results show that the GO obtained in Preparation Example 1 has a clear diffraction peak near 2θ of 11°; while rGO does not have this diffraction peak, but has a broad diffraction peak near 2θ of 24°, which indicates that the rGO obtained in Preparation Example 1 has a high reduction rate. Figure 3 (b) is the X-ray diffraction pattern of MoSe2 particles. The results show that the MoSe2 particles obtained in Preparation Example 2 have diffraction peaks of MoSe2's [0, 0, 2], [1, 0, 0], [1, 0, 2] and [1, 1, 0] crystal planes at 2θ of 13.60±0.5°, 31.52±0.5°, 37.72±0.5° and 55.67±0.5°, which indicates that the purity of the MoSe2 particles obtained in Preparation Example 2 is very high (about 95% or higher).
[0058] Raman spectroscopy analysis: Raman spectrometer was used at 150 cm -1 Up to 1000cm -1 The Raman spectra of each sample were measured in the frequency range (excitation wavelength: 154 nm). The results are as follows Figure 4 As shown, Figure 4 The horizontal axis is the Raman frequency, in cm -1 ; The vertical axis is relative intensity, in arbitrary units. Figure 4 (a) shows the Raman spectra of GO and rGO. The results show that the centers of the D band and G band of GO prepared in Preparation Example 1 are 1354±1 cm -1 and 1598±1cm -1 , while the centers of the D and G bands of the rGO prepared in Preparation Example 1 are 1351±1 cm -1 and 1602±1cm -1 In nanocarbon materials, the D band (symmetric A 1g mode) and G band (sp 2 E of carbon atom2g The change in the relative intensity of the mode can indicate the change in the electronic bonding state. The G band of GO is slightly stronger than the D band, while the D band of rGO is slightly stronger than the G band (D band intensity / G band intensity is greater), indicating that the reaction of GO reduction to rGO is significant. In addition, Figure 4 (b) is the Raman spectrum of MoSe2 obtained in Preparation Example 2. From this spectrum, it can be confirmed that MoSe2 has nanosheet structure characteristics. It can be seen from the figure that the MoSe2 particles obtained in Preparation Example 2 have a Raman spectrum of 246±1cm -1 and 284±1cm -1 There are two peaks at the center, representing the out-of-plane A of MoSe2. 1g and the in-plane plane E 2g The vibration mode shows that the MoSe2 particles in Preparation Example 2 have a nanosheet structure, and the peak value is red-shifted compared with the general bulk molybdenum diselenide (MoSe2) material.
[0059] X-ray photoelectron spectroscopy (XPS) analysis: X-ray diffraction analyzer was used to measure the photoelectron spectroscopy (XPS) of each sample in the binding energy range of 0 to 1000. Figure 5 As shown, Figure 5 The horizontal axis is the binding energy, in electron volts; the vertical axis is the relative intensity, in arbitrary units. Figure 5 (a) and Figure 5 (b) is the binding energy diagram of C1s bond of GO and rGO during X-ray photoelectron spectroscopy analysis. The results show that the peaks of C1s binding representing carboxyl carbon at 288.7±0.3eV and C1s binding representing hydroxyl at 287.7eV±0.3eV are strong in GO, while the intensity of these peaks is significantly reduced in rGO, and the peak of C1s binding representing CC or C=C bond appears significantly at 284.5±0.3eV, which indicates that most of the oxygen-containing functional groups in GO are removed and reduced to rGO. In addition, Figure 5 (c) and (d) are the binding energy diagrams of Mo3d and Se3d bonds of MoSe2 particles prepared in Preparation Example 2 during X-ray photoelectron spectroscopy analysis. MoSe2 has the corresponding Mo3d at 232.15±0.3eV and 229.08±0.3eV. 3 / 2 and Mo3d 5 / 2 orbital, which indicates that molybdenum (Mo) exists in a tetravalent (+4) form. At the same time, MoSe2 has peaks corresponding to Se3d at 55.4±0.3eV and 54.68±0.3eV. 3 / 2 and Se3d 5 / 2 orbital, which indicates that selenium (Se) exists in a negative divalent (-2) state.
[0060] Preparation of MoSe2 Nano-carbon Material Composites from Example 1 to Example 8: The MoSe2 particles obtained in Preparation Example 2 were dispersed in dimethylformamide (DMF) at a concentration of 1 mg / mL; the concentrations of the GO dispersion and rGO dispersion obtained in Preparation Example 1 were adjusted to 1 mg / mL, and 1 mg / mL of the MoSe2 particle dispersion was added and mixed in the amount shown in Table 1, and the mixed solution was treated with ultrasound at a frequency of 40±1 Hz at room temperature (22±1°C) for 1 hour, and then the mixed solution was filtered, and the filtrate was dried under reduced pressure to obtain the molybdenum diselenide nanocarbon material composites of Examples 1 to 8.
[0061] Table 1 Nanocarbon Materials <![CDATA[Mixing ratio of nano-carbon material dispersion and MoSe2 particle dispersion]]> <![CDATA[Weight ratio of carbon nanomaterials to MoSe2 particles]]> Example 1 GO 3:2 3:2 Example 2 GO 2:3 2:3 Example 3 GO 1:4 1:4 Example 4 R 3:2 3:2 Example 5 R 2:3 2:3 Example 6 R 1:4 1:4 Example 7 GO 4:1 4:1 Example 8 R 4:1 4:1 Comparative Example 1: The concentration of the GO dispersion obtained in Preparation Example 1 was adjusted to 1 mg / mL.
[0062] Comparative Example 2: The concentration of the rGO dispersion obtained in Preparation Example 1 was adjusted to 1 mg / mL.
[0063] Comparative Example 3: The MoSe2 particles obtained in Preparation Example 2 were dispersed in dimethylformamide (DMF) at a concentration of 1 mg / mL.
[0064] Transmission Electron Microscope (TEM) Analysis: In order to evaluate the structure of the MoSe2 particles prepared in the present invention, the particles in Comparative Example 3 (MoSe2 dispersion) were analyzed by TEM. Figure 6 TEM image of the catalyst of Comparative Example 3. Figure 6 In (a), (b), and (c), under different magnifications, Comparative Example 3 contains nano-sheet MoSe2 particles with a particle size of 2nm to 10nm, which is consistent with the results obtained in XRD. In addition, elemental analysis of Comparative Example 3 was performed to obtain energy dispersive X-ray spectroscopy (EDX) images as shown in the following figure: Figure 7 As shown, Figure 7 (a) is the original image of the sample under a transmission electron microscope. Figure 7 (b) shows the distribution of molybdenum. Figure 7 (c) Shows the distribution of selenium elements. The composition analysis results show that molybdenum (Mo) and selenium (Se) are evenly distributed throughout the MoSe2 nanosheets.
[0065] Scanning electron microscope (SEM) analysis: In order to evaluate the prepared MoSe2 particles, nanocarbon materials and the composite structure of the two, the surface morphology of Comparative Example 1 (GO dispersion), Comparative Example 2 (rGO dispersion), Comparative Example 3 (MoSe2 dispersion), Example 1 (GO / MoSe2=3:2) and Example 5 (rGO / MoSe2=2:3) after coating on a silicon substrate was analyzed by SEM. Figure 8It can be found that the particle size of MoSe2 particles in Comparative Example 3 is about 2μm to 5μm, but it is easy to aggregate and form large particles on the Si substrate. After compounding with GO or rGO, the composite materials (MoSe2 nanocarbon material composites) of Examples 1 and 5 can be evenly distributed on the entire Si substrate, which shows that the composite of GO or rGO with nano MoSe2 particles can improve the agglomeration problem of MoSe2 particles with catalytic activity, which is conducive to exposing more active sites of MoSe2 particles, thereby improving its catalytic activity. Compared with MoSe2 composites reported in other works, our hybrid process is expected to have significant advantages in efficiency, ease of operation and scalability.
[0066] HER (hydrogen evolution reaction) performance evaluation: In order to evaluate the HER performance of the material of the present invention, the following experiments were conducted: 1. Prepare a three-electrode system for hydrogen evolution reaction measurement, including a saturated calomel electrode immersed in 0.5M sulfuric acid electrolyte, a graphite rod counter electrode, and a 3mm diameter glassy carbon electrode. The potential measured by the saturated calomel electrode (SCE) is calibrated to the reversible hydrogen electrode (RHE) using the following formula: V RHE = V SCE + 0.0591·pH.
[0067] 2. The composite materials obtained in Examples 1 to 6 were independently dispersed in dimethylformamide (DMF) at a concentration of 1 mg / ml, and ultrasonically treated for 10 minutes at the same time as Comparative Examples 1 to 3. Then, 5 μl of the solution was drop-casted onto the glassy carbon working electrode of the hydrogen evolution reaction meter. After drying, 5 μl of Nafion solution (concentration: 5 wt%) was added dropwise and further dried.
[0068] 3. Perform linear scanning voltammetry (LSV) scanning on the electrode at a scanning rate of 5mV / s and relative to the reversible hydrogen electrode (RHE) in the voltage range of 0.2V to -1.0V (the horizontal axis is only drawn from 0.2V to -0.4V when drawing the graph) to obtain the linear scanning potential curve ( Fig. 9 (a) and Fig. 9 (b)) and Tafel plot ( Fig. 9 (c) and Fig. 9 (d)). Fig. 9 (a) and Fig. 9 In (b), the abscissa is the potential (relative to the reversible hydrogen electrode) in volts; the ordinate is the current density in milliamperes per square centimeter. Fig. 9 (c) and Fig. 9 In (d), the horizontal axis is Fig. 9 (a) and Fig. 9The absolute value of the ordinate of (b) is the logarithm to the base 10, with the unit being milliamperes per square centimeter; the ordinate is the overpotential, with the unit being volts.
[0069] 4. In order to study the reaction and electron transfer kinetics at the electrode / solution interface during the hydrogen evolution reaction, a 0.27V RHE The Nyquist plot was fitted with the equivalent circuit to determine the charge transfer resistance (R ct ), and measured electrochemical impedance spectroscopy (EIS).
[0070] 5. Cyclic voltammetry (CV) measurements were performed on electrodes respectively comprising the composite material of Example 1, the composite material of Example 5, Comparative Example 1, Comparative Example 2, and Comparative Example 3, and polarization curves were measured at the beginning of the hydrogen evolution reaction and after 1000 cycles at a scan rate of 50 mV / s relative to the reversible hydrogen electrode (RHE) between -0.4 V and 0.2 V.
[0071] The above measurement results are shown in Table 2 and Figures 9 to 11 shown.
[0072] Table 2 Nanocarbon Materials <![CDATA[Weight ratio of carbon nanomaterials and MoSe2]]> <![CDATA[η1[mV]]]> <![CDATA[η 10 [mV]]]> Tafel slope [mV / dec] <![CDATA[R ct [Ωcm 2 ]]]> Example 1 GO 3:2 180 238 57 35.4 Example 2 GO 2:3 190 248 63 54.7 Example 3 GO 1:4 195 264 67 118 Example 4 R 3:2 202 274 70 134 Example 5 R 2:3 194 261 66 79.1 Example 6 R 1:4 194 256 67 89.6 Example 7 GO 4:1 210 293 89 176 Example 8 R 4:1 255 349 88 148 Comparative Example 1 GO 1:0 -43 333 164 819 Comparative Example 2 R 1:0 -304 295 166 476 Comparative Example 3 - 0:1 210 295 80 134 From Table 2 and Fig. 9 , Fig.10 , Fig.11 ( Fig. 9 and Fig.10 In the example, the left side of the dividing line indicates an embodiment or comparative example in which rGO dispersion is not added, and the right side of the dividing line indicates an embodiment or comparative example in which GO dispersion is not added) It can be seen that the molybdenum diselenide nanocarbon material composite of the present invention has excellent activity as a catalyst for hydrogen evolution reaction. Specifically, referring to Table 2 and Fig. 9 (a) and (b), MoSe2 particles of Comparative Example 3 at a cathode current density of 1 mA / cm 2 The overvoltage (η1) at 10 mA / cm2 is slightly higher, about 210 mV; however, in the examples obtained by mixing with a certain proportion of GO or rGO, the composite material exhibits an overpotential of less than 200 mV. 2 At a cathode current density (generally considered to be an indicator of hydrogen evolution reaction performance), the MoSe2 particles of Comparative Example 3 have an overpotential (η 10 ) 295mV, while the composite material of the embodiment has a low overpotential below 275mV. In addition, Fig. 9The Tafel plots in (c) and (d) show that Example 7 and Example 8 (composite materials having a high proportion of nanocarbon material) have a high Tafel slope compared with other examples (composite materials containing a normal proportion of nanocarbon material and MoSe2 particles), while the composite materials of Example 1, Example 2 and Example 5 having a weight ratio of nanocarbon material to MoSe2 particles of 3:2 to 2:3 have a significantly lower Tafel slope. As the mixing ratio changes, the trend of the Tafel slope is consistent with the trend of the linear scanning potential, indicating that the composite materials obtained by mixing in appropriate proportions have better catalytic activity in the hydrogen evolution reaction (HER).
[0073] Fig.10 (e) and (f) show the EIS test results of the materials. The results show that the composite materials of Example 1 and Example 5 with a weight ratio of nanocarbon material to MoSe2 of 3:2 to 2:3 exhibited 35.4Ωcm 2 and 79.1Ωcm 2 Low R ct Value. ct is a correlation value showing the electrocatalytic reaction rate at the interface between MoSe2 particles and electrolyte, R ct The lower the value, the faster the electron transfer at the interface. Such results indicate that the nanocarbon material contained in the composite material can promote the electron transfer between MoSe2 particles and the electrolyte, thereby improving its hydrogen evolution performance.
[0074] Fig.11 The polarization curves of the electrodes containing the composite materials of Example 1 and Example 5 at the beginning of HER and after 1000 cycles are measured. It can be seen that the composite materials have excellent electrical stability, and even after 1000 cycles of HER, they still show a polarization curve similar to the initial curve. From these results, it can be seen that the composite materials prepared according to the present invention have excellent activity as hydrogen evolution reaction catalysts.
[0075] In the description of this specification, the description with reference to the terms "one embodiment", "certain embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0076] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a molybdenum diselenide nano-carbon material composite, characterized in that: The following steps are involved: preparing a nanocarbon material dispersion; preparing a dispersion of nano-molybdenum diselenide particles; Mixing the nano-carbon material dispersion and the nano-molybdenum diselenide particle dispersion, ultrasonically treating, filtering and drying to obtain the molybdenum diselenide nano-carbon material composite; The steps of preparing the nano-molybdenum diselenide particle dispersion liquid include: A molybdenum precursor solution at room temperature is added dropwise to a selenium precursor solution at 150°C to 200°C, and then heat-treated at 200°C to 250°C to obtain molybdenum diselenide particles after impurity removal. The molybdenum diselenide particles are dispersed in a second solvent to obtain the nano molybdenum diselenide particle dispersion.
2. The method for preparing the molybdenum diselenide nano-carbon material composite according to claim 1, characterized in that: In the step of mixing the nano-carbon material dispersion and the nano-molybdenum diselenide particle dispersion, the mass ratio of the nano-carbon material in the nano-carbon material dispersion to the nano-molybdenum diselenide particles in the nano-molybdenum diselenide particle dispersion is 100:25-400.
3. The method for preparing the molybdenum diselenide nano-carbon material composite according to claim 1, characterized in that: The solute of the selenium precursor solution is selenium powder, and the solvent of the selenium precursor solution is a mixture of oleylamine and dodecyl mercaptan in a ratio of 9:1 by volume.
4. The method for preparing the molybdenum diselenide nano-carbon material composite according to claim 1, characterized in that: The solute of the molybdenum precursor solution is molybdenum hexacarbonyl, and the solvent of the molybdenum precursor solution is a mixture of oleic acid and acetone in a ratio of 3:4 by volume.
5. The method for preparing the molybdenum diselenide nano-carbon material composite according to claim 1, characterized in that: The step of heat treatment at 200°C-250°C includes: heating to 200°C and then keeping the temperature for 30 minutes for a first heat treatment, and then heating to 250°C and then keeping the temperature for 30 minutes for a second heat treatment.
6. The method for preparing the molybdenum diselenide nano-carbon material composite according to claim 1, characterized in that: The nano-carbon material in the nano-carbon material dispersion is graphene oxide or reduced graphene oxide.
7. The method for preparing the molybdenum diselenide nano-carbon material composite according to claim 6, characterized in that: The step of preparing the nano carbon material dispersion comprises: Adding graphite powder and sodium nitrate to concentrated sulfuric acid containing potassium permanganate, stirring in an ice bath, then heating to 95° C., removing unreacted potassium permanganate with hydrogen peroxide, washing the reaction mixture with water, and then ultrasonically dispersing it in a first solvent to obtain a graphene oxide dispersion; Alternatively, L-ascorbic acid is continuously added to the graphene oxide dispersion to obtain a reduced graphene oxide dispersion after reaction.
8. A molybdenum diselenide nano-carbon material composite, characterized in that: The molybdenum diselenide nano-carbon material composite is prepared by the preparation method of any one of claims 1 to 7.
9. The molybdenum diselenide nano-carbon material composite according to claim 8, characterized in that: The invention comprises a nano-carbon material and molybdenum diselenide particles dispersedly loaded on the nano-carbon material, wherein the average size of the molybdenum diselenide particles is 1nm-20nm, wherein the molybdenum diselenide particles of 2nm-16nm account for 95%-98% of the total number of the molybdenum diselenide particles.
10. A hydrogen evolution catalytic electrode, characterized in that: Contains the molybdenum diselenide nano-carbon material composite as claimed in claim 9.
Citation Information
Cited By
Method and device for enhancing catalytic oxidation of volatile organic compounds by electric field based on molybdenum-based cathode electrode
CN121490542A